Terrorist Incidents in India, 1998–2004: A Quantitative Analysis of Fatality Rates - Borooah, Vani
Using data from the University of Maryland’s Global Terrorism Database II, this paper first provides information on the nature of terrorist incidents in India in the period 1998-2004: the Indian states that were worst affected by terrorist incidents and fatalities; the terrorist groups responsible for such incidents and their modus operandi. Next, the paper focuses on the issue of fatalities from terrorist incidents. It inquires into the extent to which the number of fatalities following an incident was influenced by the type of attack (bombings, armed assault, etc.) and the extent to which it was influenced by the type of terrorist group. By examining the number of fatalities resulting from terrorist attacks in India, the paper disentangles the influence on this number of attack type and attack group. Lastly, the paper applies Atkinson’s concept of equality-adjusted income to terrorism to arrive at the concept of equality-adjusted deaths from terrorist incidents: in order to avoid spectacular incidents resulting in the loss of a large number of lives—as in New York on September 11, 2001 and in Mumbai 26–29 November 2008—‘‘society’’ might be prepared to tolerate ‘‘low-grade’’ terrorism which resulted in a larger number of deaths in total but avoided a large number of deaths from a single iconic incident.attack type, India, terrorism, terrorist groups